Effects of Achievement Motivation, Self-Efficacy, and Self-Concept on the Adversity Quotient - Dwi Puji Astuti; Anna Kania Widiatami; Anis Susanti (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
This study was conducted to determine and analyze the adversity quotient in economic education students with factors that affect the adversity quotient, including achievement motivation, self-efficacy and self-concept. All of these factors can be influenced by a person's self-concept. The approach used, quantitative methods. The population of this study is students of Economic Education, Faculty of Economics and Business, Universitas Negeri Semarang with a total of 437 students. The sampling technique uses non-probablity sampling. The results showed that there is an influence of prestige motivation on adversity quotient, there is an influence of self-efficacy on adversity quotient, there is no influence of self-concept in strengthening the influence of achievement motivation on adversity quotient, there is an influence of self-concept in weakening self-efficacy on adversity quotient. The suggestion for this study is that students must maintain their achievement motivation and self-efficacy and control their self-concept in order to overcome all difficulties and achieve what they aspire to.